Microplastic accumulation, morpho-polymer characterization, and dietary exposure in urban tap water of a developing nation - Hossain, M. Belal; Yu, Jimmy; Sarker, Pallab Kumer; Banik, Partho; Sultana, Salma; Nur, As-Ad Ujjaman; Haque, Md. Rashedul; Rahman, Md. Mostafizur; Paray, Bilal Ahamad; Arai, Takaomi (Frontiers in Sustainable Food Systems, 2024)
The recent detection of microplastics (MPs) in a large number of commercially important food items and beverages, including tap water, has drawn significant attention because of direct exposure and negative health effects on humans. Nevertheless, there is insufficient information on microplastic contamination in the tap water of developing countries. In the present study, we primarily analyzed supplied tap water samples from four major cities in Bangladesh to determine, and characterize MPs using stereomicroscope and Fourier transform infrared spectroscopy (FTIR). Several indices were employed to calculate human health exposures to microplastics. MPs were found in all of the water samples tested, with an overall mean of 35.33 ± 19.55 particle/L. The results of this study diverge from those of comparable research conducted globally, revealing that tap water in Bangladesh exhibited higher levels of contamination compared to other nations. MPs were found in three different shapes (fibres, fragments and films), with fibres dominating the samples (96.2%), and 98.1% of the microplastics were less than 0.5 mm in size. Six different colours of MPs were observed, and transparent particles were dominant (63.9% of all observed MPs). FTIR infrared spectrum analysis revealed two major types of polymers: low-density polyethylene (LDPE) and high-density polyethylene (HDPE). The projected daily consumption of microplastics was determined to be 2.65 particles per person per day, raising potential concerns for human health.. The findings show that the treatment process of the water supply system is inadequate. Additionally, the sources of microplastics in tap water may come from where the water was collected for treatment and may be linked to a variety of anthropogenic activities, such as urbanization, sewage discharge, industrial waste disposal, and runoff from catchment areas.